Uso do mapa da empatia em saúde como facilitador do desenvolvimento de empatia em estudantes de medicina: estudo quase experimental - Sousa, Luíza Uchôa de Resende (2020)
Introduction: The good doctor-patient relationship presents therapeutic purposes, and empathy is amongst its principles, as it’s a fundamental part and it allows the doctor to comprehend the inner experiences and understand the patient as a singular subject. Despite the difficulty in conceptualizing, measuring and teaching empathy, it’s been the subject of several researches in the health teaching area in the lastest years. The empathy development throughout graduation has the objective of making graduates more prepared to build of a good relationship with their patients. The Health Empathy Map (HEM) is an adapted tool with the purpose of developing, through self-reflection, empathy in students and doctors to-be. Objectives: Evaluate the effects of the use of HEM as an empathy facilitator on Medicine students. Method: This is a nearly experimental and qualitative study carried out with 56 Medicine students from the fifth term of the José do Rosário Vellano University (UNIFENAS-BH). The students were divided into two groups: G1: students who used HEM in the tutorial group strategy (TG) on the cardiological syndromes block; G2: control, students who did not use HEM in the TG on the same block. All students filled in a sociodemographic questionnaire in the beginning of the block and the students’ version of Jefferson Scale of Empathy in the beginning and end of the discipline. Statistical analysis were carried out to compare the global empathy score and by domains between the groups, and at the different stages of the study. The content analysis of some maps was based on categorization according to Bardin. Results: The students’ level of empathy was raised and there was no statistical difference in the two study stages. On the map content analysis, it was possible to identify three major themes: (1) awareness of their own feelings with regard to the patient’s case (2) perception of the patient’s desires and needs and (3) therapeutic conduct. It was also possible to verify the differences in the students’ perceptions about the problems experienced by the patient, as some of them focused solely on the disease, while most of them could realize the importance of the psychosocial aspects involved. Conclusion: The use of HEM, in the TG, did not promote the rise of empathy scores on the analysed students. Despite that, the map content analysis pointed out the different students’ perceptions regarding the patient which vary from perceptions more focused on the disease to the broader ones, involving psychosocial aspects. Therefore, HEM has shown to be a useful tool to be utilized in order to facilitate the empathy development in the tutorial group scenario on Medicine students